(untitled) (مجلة الفاروق للعلوم, 2026)
This study investigates the relationship between teachers’ oral corrective feedback (OCF) and students ’ responses in English as a foreign language EFL speaking classes at Janzour, Libya through a qualitative discourse-analytic approach. Located within the wider area of classroom interaction research and rooted in the theoretical orientations of Conversation Analysis (CA) and Systemic Functional Linguistics (SFL), the study aims to describe and interpret the types of feedback strategies deployed by EFL speaking teachers, how students orient to and respond to those strategies, and the socio-cultural and institutional mechanisms that mediate the feedback-uptake dynamic in the Libyan higher education context. Data will be collected via naturalistic audio recording of speaking lessons and semi-structured interviews with participating teachers and students. The research reveals that